Navigating the Currents: The Language Ecology of Limbang Bisaya - Chong, Shin; Dilah, Tuah; Yao, Ling; Pan, Hui; Ng, Boon Sim (RSIS International, 2025)
The discipline of ecolinguistics, also known as language ecology, is a field pioneered by Haugen (1972). It uses environmental ecology as a metaphor for a language's environment, focusing on key topics such as language diversity, the challenges faced by minority languages, and language preservation and loss. This paper explores the language ecology of the Bisaya, a minority ethnic group in Limbang, Sarawak. A literature review reveals that studies on the Bisaya language are very limited, and the language's vitality status remains unknown. To identify this status, the study employs interviews and observation to understand the position of Bisaya within its multilingual environment. The findings indicate that the languages present in the Bisaya language ecology are Iban, the Sarawak Malay dialect, the Brunei Malay dialect, and Colloquial Malay. Within this linguistically diverse ecology, Bisaya speakers generally master these languages for various interactional purposes. They also maintain a good command of their native Bisaya language, although signs of decline are present. The survey confirms that the Bisaya mother tongue remains the primary language of interaction within the community. Ultimately, the choice of an external language is highly dependent on the domain and the interlocutor's background.